Adsorption and desorption effect of modified bentonite on soil heavy metal Pb/Cd and the feasibility assessment of reducing the ecotoxicity - Xue Yang; Yuancheng Li; Maoxi Gan; Yuling Chen; Hailong Meng; Lun Li; Jianhong Xu; Meihong Zhao; Dongpeng Lv (Environmental Sciences Europe)
Abstract Background Lead and cadmium (Pb/Cd) are pervasive in soils, and their detrimental effects on ecosystems are increasingly evident. Therefore, taking measures to mitigate the toxicity of Pb/Cd is urgently necessary. In this study, bentonite was used as a raw material for modification, and the influence of modified bentonite on the soil adsorption and desorption of Pb/Cd was investigated. The potential application of modified bentonite in mitigating the phytotoxicity of Pb/Cd was evaluated by conducting pot experiments, and the environmental risk was evaluated by acid rain leaching test. Results Results indicate that the removal rates of Pb/Cd of BTS obtained by 450℃ calcination and 20% citric acid activation reached 88.03% and 80.04%, respectively. Pb/Cd was primarily adsorbed by BTS through coordination between the groups (e.g., siloxane, hydroxyl, and carboxyl) and Pb/Cd. BTS amendment at an appropriate concentration (1%, 3%, and 5%, w/w) to soils contaminated with Pb/Cd resulted in a significant increase in ryegrass yield and chlorophyll (P < 0.05), and it enhanced root activity and antioxidant enzyme activity. Furthermore, under the effect of acid rain at pH 5.0, the release concentrations of Pb/Cd were the lowest when BTS-5% was added, and the cumulative release concentrations were 2.079 and 1.506 mg·L−1, respectively. The extractable acid state increased before and after leaching, whereas the residual state decreased. Conclusion BTS (3% and 5%) can reduce the environmental risk level from a strong risk to a slight risk. Furthermore, the results of this study can provide theoretical basis for the promotion and application of bentonite in pollution control.